Settlement of Debts through Compulsory Set-off - Al-Omari, Mohammad Ali; Rababa, Basma Ali (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This study aims to explore the possibility of debt settlement through compulsory set-off, including defining the concept, legitimacy, and conditions of compulsory set-off. It also seeks to understand the perspectives of jurists on this matter and highlight some of its juristic forms or applications. Methods: The study followed the inductive and deductive methodology by reviewing and analyzing texts related to the study’s topic. It also employed a comparative approach to compare juristic opinions and clarify the prevailing ones. Results: The study yielded several results, including the finding that compulsory set-off is a shortcut for resolving many problems arising from the issue of settling overdue debts. The study indicated two main trends among jurists: the first trend, supported by the majority of Hanafi, Shafi’i, and Hanbali scholars, asserts the permissibility of settling debts through compulsory set-off. The second trend, advocated by the Maliki school, denies its permissibility. The researchers argued in favor of adopting compulsory set-off in debt settlement, as it aligns with the principle of clearing obligations, alleviating burden and hardship for both creditors. Conclusion: Compulsory set-off occurs between two equal and similar debts in terms of type, amount, maturity, and resolution. It contributes to solving debt-related problems, cutting off the roots of conflict and disagreement between debtors.